Complete Mitochondrial Genome of Trichuris trichiura from Macaca sylvanus and Papio papio - Rivero, Julia (Life (Basel), 2021)
Trichuriasis is among the most prevalent worldwide parasitism caused by helminths. For many years, Trichuris spp. have been described with a relatively narrow range of both morphological and biometrical features. The use of the complete mitochondrial genome (mitogenome) is an alternative and powerful molecular method for inferring phylogenies. Here, we present an overview of the contributions of mitogenome for Trichuris spp. from human and non-human primates. In addition, we carry out structural and phylogenetic comparative analyses with genomes of Trichuris species available in public datasets. The complete mt genomes of Trichuris trichiura and Trichuris sp. from Macaca sylvanus and T. trichiura from Papio papio are 14,091 bp, 14,047 bp and 14,089 bp in length, respectively. The three mt genomes are circular and consist of 37 genes—13 PCGs (cox1–3, nad1–6, nad4L, atp6, atp8 and cob), 22 transfer RNA genes (tRNAs), and two rRNAs (rrnL and rrnS). The molecular evidence presented here supports the hypothesis that T. trichiura de M. sylvanus (TMF31) and T. trichiura de P. papio (TPM1) were similar but genetically different with respect to Trichuris sp. from macaques (TMM5). The phylogenetic study also supported the evolution of the different Trichuris species. In conclusion, we suggest the existence of two cryptic species parasitizing M. sylvanus.